Identification of bioaccessible and uptaken phenolic compounds from strawberry fruits in in vitro digestion/Caco-2 absorption model. (1st March 2015) - Kosińska-Cagnazzo, Agnieszka; Diering, Sascha; Prim, Denis; Andlauer, Wilfried
Highlights: Pelargonidin-3-glucoside is the most abundant compound accessible for uptake in strawberries. Sulphate and glucuronide conjugates are formed in Caco-2 cells. Coumaric acid derivatives are transported through intestinal epithelium. Abstract: Strawberry fruits are highly valued for their taste and nutritional value. However, results describing the bioaccessibility and intestinal absorption of phenolic compounds from strawberries are still scarce. In our study, a combined in vitro digestion/Caco-2 absorption model was used to mimic physiological conditions in the gastrointestinal track and identify compounds transported across intestinal epithelium. In the course of digestion, the loss of anthocyanins was noted whilst pelargonidin-3-glucoside remained the most abundant compound, amounting to nearly 12 mg per 100 g of digested strawberries. Digestion increased the amount of ellagic acid available by nearly 50%, probably due to decomposition of ellagitannins. Only trace amounts of pelargonidin-3-glucoside were found to be absorbed in the intestine model. Dihydrocoumaric acid sulphate and p -coumaric acid were identified as metabolites formed in enterocytes and released at the serosal side of the model.